Thermochromic Latent‐Pigment‐Based Time–Temperature Indicators for Perishable Goods. Issue 9 (8th June 2015) - Galliani, Daniela; Mascheroni, Luca; Sassi, Mauro; Turrisi, Riccardo; Lorenzi, Roberto; Scaccabarozzi, Alberto; Stingelin, Natalie; Beverina, Luca
<x xml:space="preserve">Abstract</x> The development of cheap and reliable time–temperature indicators (TTIs) can greatly improve customer satisfaction with respect to the correct handling and storage of perishable goods. A series of new irreversible thermochromic squaraine dyes enables the preparation of simple TTIs whose time–temperature regime can be controlled by selection of the appropriate molecule/substrate combinations.